2022
DOI: 10.1002/jaba.956
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of treatment duration on the resurgence of destructive behavior

Abstract: Translation of promising procedures for mitigating treatment relapse has received considerable attention recently from researchers across the basic–applied continuum. One procedure that has demonstrated mixed support involves increasing the duration of treatment as a strategy for blunting resurgence. In a recent translational study, Greer et al. (2020) failed to detect a mitigation effect of increased treatment duration on the resurgence of destructive behavior. However, design limitations may have been respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Fisher et al (2018) observed less resurgence of problem behavior exhibited by individuals with ASD when using an FCT treatment package informed by BMT that incorporated lean schedules of reinforcement compared with dense schedules. Note, though, that Fisher et al (2018) also manipulated baseline rates of reinforcement for problem behavior and phase duration in BMT‐informed FCT, the latter of which has resulted in discordant findings in terms of mitigating resurgence (see Greer et al, 2020; Greer et al, 2022). Although the lean DRA schedules were surely responsible in part for mitigating resurgence, it is difficult to determine the full extent to which lean DRA accounted for less resurgence.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher et al (2018) observed less resurgence of problem behavior exhibited by individuals with ASD when using an FCT treatment package informed by BMT that incorporated lean schedules of reinforcement compared with dense schedules. Note, though, that Fisher et al (2018) also manipulated baseline rates of reinforcement for problem behavior and phase duration in BMT‐informed FCT, the latter of which has resulted in discordant findings in terms of mitigating resurgence (see Greer et al, 2020; Greer et al, 2022). Although the lean DRA schedules were surely responsible in part for mitigating resurgence, it is difficult to determine the full extent to which lean DRA accounted for less resurgence.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these frameworks and models can allow predictions of how subtle changes to stimulus and reinforcement conditions may increase or decrease the likelihood and magnitude of relapse (Fisher et al, 2022). Accordingly, these frameworks and models have sparked systematic lines of research examining the clinical utility of procedures designed specifically to mitigate relapse (e.g., Fisher, Greer, Fuhrman et al, 2018; Fisher et al, 2019; Fuhrman et al, 2016; Greer et al, 2020; Greer, Shahan, et al, 2022). These lines of research are imperative, given recent calls from applied researchers and clinicians for answers concerning relapse mitigation (Kestner & Peterson, 2017; Ringdahl & St. Peter, 2017).…”
Section: Quantitative Theories and A Narrative Account Of Relapsementioning
confidence: 99%
“…Evaluations with humans have also demonstrated mixed effects of short versus long exposure to DRA during treatment Greer et al, 2020;Greer, Shahan, et al, 2022;Smith & Greer, 2022;Wacker et al, 2011). In an investigation on the effects of both baseline and treatment durations, Smith and Greer (2022) found that 20 min of DRA in Phase 2 contributed to less resurgence in Phase 3 than 5 min of DRA in a computer task with human participants.…”
Section: Duration Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A follow‐up study by Greer et al (2023) evaluated the effects of treatment duration using a sequential design and more extreme duration discrepancies but also did not replicate the predictions of BMT. The collective findings to date suggest that the robust mitigation of resurgence of destructive behavior observed by Fisher, Greer, Fuhrman, et al (2018) was likely determined, in part, by lowering the rate of reinforcement for destructive behavior in Phase 1, as evidenced by the results of Fisher et al (2019), but was unlikely to have been a result of increasing the duration of treatment, as suggested by the results of Greer et al (2020) and Greer et al (2023).…”
mentioning
confidence: 99%